Pengaruh Ekstrak Lengkuas Putih [Alpinia galanga (L.) Willd] terhadap Infeksi Trichophyton mentagrophytes pada Kelinci - DJAENUDIN GHOLIB; DARMONO DARMONO (Fakultas Farmasi Universitas Pancasila, 2008)
Lengkuas putih [Alpinia galanga (L.) Willd] has long been known to be used in treatment of dermatophytosis, a skin disease caused by dermatophytes fungi such as Trichophyton mentagrophytes. The fungi infects hairs, skins, and nails that contain keratin. The study was conducted in order to measure the effect of ethanol extract of Alpinia galanga in inhibiting Trichophyton mentagrohytes colonies both through in vitro test and in vivo test using infected rabbits . The results showed that minimal inhibition concentration (MIC) of Ahoinia galanga extract Was 1.5%. The extract was administered in cream preparation on in vivo test with minimal concentration (1.5%). Three group of rabbits were treated with the extract cream preparation (Group I), 2% with ketokonazol cream (Group II, positive control), and With none (Group III, negative control), respectively. The results showed that the infected rabbits treated with either cream containing the extract or ketokonazol were better recovered from infection than the rabbits in negative control group.